Research on Abnormal Behavior Recognition of Buses Based on Improved Support Vector Machine - Yong Pan; Xiangmo Zhao; Zhigang Xu; Junwei Li; Yifei Li; Li Liu (Journal of Advanced Transportation)
The abnormal driving behavior of buses brings about greater security threat. How to effectively identify the abnormal driving behavior of buses has become one of the problems of cracking public transportation safety. This paper constructs an abnormal behavior recognition model of buses based on improved support vector machine. Through the verification, the model has a high recognition rate, which provides an important means for further improving the safety of public transportation operations.